1956
DOI: 10.1007/bf02638203
|View full text |Cite
|
Sign up to set email alerts
|

The hydrogenation of dietary unsaturated fatty acids by the ruminant

Abstract: SummaryGoats were fed alfalfa meal containing 10% cottonseed or linseed oil. After 11 weeks the fatty acids of rumen, stomach, and caecum contents were compared to those of the feed.It was found that the high levels of linoleic and linolenic acis of the feed were reduced to very low levels in the rumen, with comparable increases in the saturated acids. Monoethenoid acids were increased after linseed oil ingestion and in one animal after cottonseed oil ingestion.The ratio of monoethenoid to saturated acids in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
4

Year Published

1961
1961
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 12 publications
1
35
0
4
Order By: Relevance
“…On the gas chromatograms their methyl esters appeared in positions between methyl laurate and methyl tridecanoate, and between the latter and methyl myristate. Whilst the studies of Shorland et al (1957) showed that unsaturated fatty acids as such were hydrogenated when they were incubated with rumen contents, the experiments so far described here do not preclude the possibility that hydrogenation might take place whilst the acids were still in glyceride combination. Though in most of the experiments with linseed oil hydrolysis was almost complete, in others (as previously mentioned) ,the extent of hydrolysis was much less.…”
Section: Glyceride Metabolism In the Sheep's Rumen 221mentioning
confidence: 67%
See 2 more Smart Citations
“…On the gas chromatograms their methyl esters appeared in positions between methyl laurate and methyl tridecanoate, and between the latter and methyl myristate. Whilst the studies of Shorland et al (1957) showed that unsaturated fatty acids as such were hydrogenated when they were incubated with rumen contents, the experiments so far described here do not preclude the possibility that hydrogenation might take place whilst the acids were still in glyceride combination. Though in most of the experiments with linseed oil hydrolysis was almost complete, in others (as previously mentioned) ,the extent of hydrolysis was much less.…”
Section: Glyceride Metabolism In the Sheep's Rumen 221mentioning
confidence: 67%
“…It should be mentioned that hydrogenation results in the production of spatial and positional isomers of unsaturated acids (Shorland et al 1957); these are included, where appropriate, in Tables 2 and 3 under the heading 'C,8 mono-, di-and tri-unsaturated acids'. Linolenic acid forms a very large proportion of the total fatty acids of pasture grasses (Garton, 1960).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BH intermediates of LNA were first observed by Reiser (1951), who found that after linseed oil was incubated with rumen sheep liquor, the LNA concentration decreased while the proportion of C18:2 and C18:1 increased. Shorland et al (1955) subsequently observed that the depot fat of grazing ruminants had a FA profile low in LNA, which is the main FA in grass.…”
Section: Conjugated Linolenic Acid Isomers Synthesis In the Rumenmentioning
confidence: 92%
“…Later, it was reported that biohydrogenation occurs in the rumen. Unsaturated fatty acids were reported to be transformed in less unsaturated fatty acids with trans double bonds [4,5]. In 1967, Kepler [6] reported that a ruminal bacteria, Butyrivibrio fibrisolvens, was able to produce conjugated 18:2 from linoleic acid.…”
Section: History Of Clamentioning
confidence: 99%